Intercultural Communication Competence Approach in Inclusive Writing BIPA Learning in Surabaya Higher Education - Rizky Abrian; Warsita Noer Ardiyanti (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study explores the BIPA (Indonesian language for non-native speakers) inclusivity in higher education, focusing on writing classes and skills through the perspective of Intercultural Communication Competence (ICC). The study, moreover, highlights the importance of acknowledging and valuing diversity in the BIPA learning class to create a supportive classroom climate for international students. Additionally, this situation can help them express themselves freely and confidently while learning Indonesian. The research depicts various teaching strategies that can be implemented during writing class, such as collaborative writing, peer review, and relevant themes categorisation groups, to learn different learning styles and cultures. Research methodology employs qualitative method by conducting semi-structured interviews to four lecturers who teach writing classes. The findings of this study are intercultural knowledge and skills, attitudes, and critical cultural awareness from BIPA lecturer perspectives in the writing class using ICC play pivotal roles. The recommendation from this research is that lecturers need to integrate ICC into their teaching practices for every language skill because it can promote a more inclusive educational environment. However, further research is required to ensure the effectiveness of ICC in other language skills.